A importância da percepção socioambiental dos professores para a construção de tecnologia social: um estudo de caso no Baixo Tocantins - PINTO, Rosilene Farias (2024)
Perception is a way to sensitize both the observer and the dissemination of what has been seen. In this process, the teacher is the main ally in understanding the environment to convey to the student, as well as solving problems, especially in traditional communities. The objective of this study was to describe the socio-environmental perception of teachers in riverside communities and, based on this perspective, promote the use of social technology. The research took place in the district of Janua Coeli in April 2023, covering 23 riverside and quilombola schools in the Municipality of Cametá. Semi-structured questionnaires were applied within a qualitative-quantitative approach. The majority of teachers consider the area to be poorly preserved, citing the extinction of some animals over time. It is noteworthy that the main environmental issue was solid waste management. All teachers consider studies on the islands important to support public management. The study highlights the need for teachers to reflect on the environment, as they are the main interveners in the classroom and, in this way, promote the use of social technology, as teachers and students with the help of social technology can solve socio-environmental problems in their riverside community.